2013
DOI: 10.5194/cp-9-335-2013
|View full text |Cite
|
Sign up to set email alerts
|

Modern isotope hydrology and controls on δD of plant leaf waxes at Lake El'gygytgyn, NE Russia

Abstract: Abstract. Stable isotope data from lipid biomarkers and diatom silica recovered from lake sediment cores hold great promise for paleoclimate and paleohydrological reconstructions. However, these records rely on accurate calibration with modern precipitation and hydrologic processes and only limited data exist on the controls on the δD values for n-alkanoic acids from plant leaf waxes. Here we investigate the stable isotopic composition of modern precipitation, streams, lake water and ice cover, and use these d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 75 publications
(165 reference statements)
1
30
0
Order By: Relevance
“…In summer 2003 the active layer varied between 0.4 m in silty material and 0.8 m in sand and gravel (Schwamborn et al, 2012). The Crater region belongs to the hypoarctic tundra vegetation zone (Yurtsev, 1973) with discontinuous cover dominated by lichen and herbaceous taxa (Kohzevnikov, 1993;Minyuk, 2005;Lozhkin et al, 2006;Wilkie et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In summer 2003 the active layer varied between 0.4 m in silty material and 0.8 m in sand and gravel (Schwamborn et al, 2012). The Crater region belongs to the hypoarctic tundra vegetation zone (Yurtsev, 1973) with discontinuous cover dominated by lichen and herbaceous taxa (Kohzevnikov, 1993;Minyuk, 2005;Lozhkin et al, 2006;Wilkie et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lower temperatures during evaporation and higher continentality of moisture originating from the Arctic Ocean and the Baltic Sea lead to further D-depletion of precipitation from these sources (Rosqvist et al 2007;Jonsson et al 2009). As previous results from Arctic environments have shown that the D/H isotopic composition of the C 26 fatty acid might be influenced by contributions of C 26 fatty acid from autochthonous production (Wilkie et al 2013), we only use the C 28 fatty acid for the palaeoclimatic reconstruction. The Tornetr€ ask compound-specific dD values of the C 28 and C 26 fatty acids (Fig.…”
Section: Hydrological Source Signaturesmentioning
confidence: 99%
“…to max. ranges; GMWL (global meteoric water line) after Craig (1961); * data from Wilkie et al (2013). 3.0 • C. Lake El'gygytgyn is similar to that: it has a measured temperature between 3 and 4 • at the bottom depending on the season (Cremer and Wagner, 2003). Time and depth dimensions of those two other sites are comparable with Lake El'gygytgyn when considering past talik growth at the lake edge.…”
Section: Interpretation Based On Permafrost and Lake Dynamicsmentioning
confidence: 99%
“…Wilkie et al (2013) have specified an annual average partitioning of precipitation in El'gygytgyn crater into 60 % winter contribution and 40 % summer input (annual average δ 18 O = −19.3 ‰, δD = −152.9 ‰). Bearing in mind this estimate and also the error bars of minimum and maximum δ values in the sample sets (Table 1, Fig.…”
Section: Ground-ice Origin: Constraints From Downcore Hydrochemical Amentioning
confidence: 99%